Effects of acute physical exercise and television viewing on mood in older active women - Christofoletti, Ana Elisa Messetti [UNESP]; Sebastião, Emerson; Ueno, Deisy Terumi [UNESP]; Bonolo, Angélica [UNESP]; Deutsch, Silvia [UNESP]; Nakamura, Priscila Missaki [UNESP] (FapUNIFESP (SciELO), 2019)
Aim: Due to the increased prevalence of mood disorders and the detrimental effects of sedentary behavior on health, a better understanding of the association between physical exercise (PE), TV viewing and mood in older adults is paramount. This is based on the fact that mood has been recognized as an important predictor of longevity, well-being, and quality of life. This study examined the effects of an acute bout of physical exercise (PE) and television viewing (TV) on positive and negative mood states of older active women. Methods: Fifty-four women aged 60 years and older were asked to complete the Abbreviated and Illustrated Mood States Inventory (LEA-RI) before and immediatly after two distinct activities: 1) single bout of PE; and 2) a single bout of TV. Participants further completed questionnaires to provide information on demographics, physical activity and sedentary behavior for sample characterization. Differences between conditions (PE and TV) on positive and negative mood state were analyzed using repeated measures ANOVA followed by paired sample t-test adopting a significance level of P<.05. Results: Positive mood states significantly increased for the PE (P=0.001) but not for the TV condition (P=0.388). Negative mood states significantly increased for the PE condition (P=0.003) but significantly reduced for the TV condition (P=0.011). Conclusions: The findings suggest that a single bout of PE may be more beneficial to improve positive mood compared to a single bout of TV. However, the TV may be able to reduce negative mood in older active women.
Keywords: Active lifestyle; Elderly; Mood; Motor activity; Sedentary behavior